The Influence of Advertising Creativity and Brand Attitudes and Their Impact on Purchasing Decisions (Shopee E-Commerce Product Purchase Case Study) - Lutfi, Lutfi Adi Prastya; Indri, Indri Juwita Sari; Jeni, Jeni Pusfitasari; Inge, Gianine Lasalandra (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The company needs the so-called competitive advantage to succeed both in the domestic and international markets, where fierce competition from other businesses is a constant threat. Rapid advances in information technology, particularly the internet, have had a far-reaching impact in many areas, including social, economic, political, and cultural fields, as well as on people's daily routines, including the way they conduct business and shop for goods. Many people in Indonesia now prefer to shop online instead of visiting physical stores. Shopee's presence in the Indonesian e-commerce market is the result of the rapid expansion of the market which attracts many new players. This research is quantitative, using multiple regression techniques, and the respondents were 117 Shopee users from Indonesia. The purpose of this study is to investigate how advertising innovations and consumer perceptions of brands displayed on Shopee's e-commerce platform influence consumers' final decision to purchase those products. Based on the adjusted r2 value of 0.561 contained in the results of the coefficient of determination test, the variation in both independent variables of advertising creativity and brand attitude can explain 56.1% of the variation in the dependent variable of purchasing decisions. The influence on the dependent variables is also indicated by the results of simultaneous significance tests (statistics of the f test). A statistical f value of 68.0369 with a probability of 0.000 is displayed in the output. We can conclude that the invention of advertising and brand attitudes influence consumer decisions because the probability is less than 0.05. The results of the t-test, which tested the relationship between two independent variables (advertising inventiveness and brand attitude), support the idea that both have an influence level of 0.05 on the final decision of consumers.